Impact of fraud and dispute management on risk mitigation and reputation establishment as a part of compliance for a mobile financial company: an analysis of bKash - Saarmean, Rubaiat (Brac University, 2021)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2021.